COMMUNICATION ETHICS LIVE TIKTOK INTERFAITH DIALOGUE IN THE PERSPECTIVE OF AL-GHAZALI'S COMMUNICATION ETHICS - Delliana, Santi; Agustrijanto, Agustrijanto; Wibowo, Antonius Mulyono (ppjbsip, 2025)
The rapid development of social media has significantly impacted interfaith dialogue, enabling discussions to transcend physical boundaries. TikTok, a popular social media platform, has become a major space for interfaith discourse, but ethical violations such as ad hominem attacks, misinformation, and disrespectful interactions often undermine productive discussions. This study critically examines communication ethics in TikToks live interfaith dialogues through the lens of Al-Ghazalis ethical communication principles. We collected data using a qualitative approach by observing TikTok live sessions and interviewing individuals involved in these discussions. Findings indicate widespread ethical violations, including personal attacks, rigid truth claims, and emotionally driven arguments. These behaviors contradict Al-Ghazalis emphasis on respectful, knowledge-based, and morally grounded communication. The study highlights the risks of religious cyber-balkanization, where social media discussions reinforce ideological divisions rather than fostering mutual understanding. Furthermore, the lack of moderation and ethical standards exacerbates these issues, reducing the potential of TikTok as a platform for constructive religious dialogue. This research contributes to the broader discourse on digital ethics by contextualizing classical Islamic communication principles within modern online interactions. It calls for platform-specific ethical guidelines, improved moderation policies, and awareness campaigns to promote respectful interfaith discussions. Future research should explore the effectiveness of AI-driven moderation tools in mitigating online hate speech while preserving open dialogue. By addressing these ethical concerns, social media forms can become more inclusive and supportive of meaningful interfaith engagement.